Respuesta :

Answer:

The explicit formula is a[tex]_{n}[/tex] = 5 - 6n

Step-by-step explanation:

The explicit formula of the arithmetic sequence of the recursive formula

a[tex]_{1}[/tex] = first term; a[tex]_{n}[/tex] = a[tex]_{n-1}[/tex] + d is a[tex]_{n}[/tex] = a + (n - 1)d, where

  • a is the first term
  • d is the common difference between each two consecutive terms
  • n is the position of the number

∵ The recursive formula is a[tex]_{1}[/tex] = -1 and a[tex]_{n}[/tex] = a[tex]_{n-1}[/tex] - 6

→ Compare it with the formula above

a = -1 ⇒ 1st term

d = -6 ⇒ common difference

→ Substitute them in the form of the explicit formula

∵ a[tex]_{n}[/tex]  = -1 + (n - 1)(-6)

∴ a[tex]_{n}[/tex] = -1 + (-6)(n) - (-6)(1)

∴ a[tex]_{n}[/tex]  = -1 + -6n - (-6)

∴ a[tex]_{n}[/tex] = -1 - 6n + 6

→ Add the like term

a[tex]_{n}[/tex] = 5 - 6n

The explicit formula is a[tex]_{n}[/tex] = 5 - 6n

ACCESS MORE